Provider opioid prescribing practices and the belief that opioids keep people living with HIV engaged in care: a cross-sectional study. Issue 9 (2nd September 2019) - Tsui, Judith I.; Walley, Alexander Y.; Cheng, Debbie M.; Lira, Marlene C.; Liebschutz, Jane M.; Forman, Leah S.; Sullivan, Margaret M.; Colasanti, Jonathan; Root, Christin; O'Connor, Kristen; Shanahan, Christopher W.; Bridden, Carly L.; et al.
ABSTRACT: We describe HIV providers' opioid prescribing practices and assess whether belief that chronic opioid therapy (COT) keeps people living with HIV (PLWH) engaged in care is associated with differences in these practices among providers from two HIV clinics. We conducted logistic regression to evaluate the association between the belief that COT keeps PLWH engaged in care and at least one component of guideline-recommended care (i.e., urine drug tests, treatment agreements, and/or prescription monitoring program use). The sample included 41 providers with a median age of 42 years, 63% female, 37% non-white. Routine adherence to guideline-recommended practices was: 34% urine drug tests, 27% treatment agreements, and 17% prescription monitoring program. Over half [54%] agreed that COT keeps PLWH engaged in care. There was no significant association between belief that COT keeps PLWH engaged in care and routinely providing any recommended COT care component (aOR 2.38; 95% CI 0.65–8.73). Most HIV providers do not routinely follow guidelines for opioid prescribing. We observed a positive association between belief that COT keeps PLWH engaged in care and following any guideline-recommended prescribing practices, although the result was not statistically significant. Interventions are needed to improve guideline-concordant care for COT by HIV providers.